2021
DOI: 10.1016/j.annonc.2021.08.1636
|View full text |Cite
|
Sign up to set email alerts
|

1643P Knowledge and attitude of cancer patients towards COVID-19 pandemic: A study from Pakistan

Abstract: receiving an oral treatment whereas only 33.5% would agree if the treatment was endovenous. In general, younger patients (<50 years old) feel more comfortable with virtual visits than older ones (>70 y) (77.4% vs 62%, p¼0.07). Only 20% of patients older than 50 believe that they can handle new technologies as opposed to 58.5% of younger ones (p¼0.001). 60.4% of the younger patients would like to have different technological tools to contact their oncologist whereas most patients (47.6%) older than 70 prefer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…In contrast to earlier research that revealed comparatively less awareness regarding COVID-19 disease transmission, the participants in this study had an excellent knowledge of COVID-19 [33][34][35][36]. Another study conducted in Pakistan showed that 99.6% of cancer patient were aware of COVID [37]. The participants' better understanding of COVID-19 was due to frequent healthcare interaction, the observation of extra preventive measures taken by health professionals, and the government's distribution of information via numerous sources.…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast to earlier research that revealed comparatively less awareness regarding COVID-19 disease transmission, the participants in this study had an excellent knowledge of COVID-19 [33][34][35][36]. Another study conducted in Pakistan showed that 99.6% of cancer patient were aware of COVID [37]. The participants' better understanding of COVID-19 was due to frequent healthcare interaction, the observation of extra preventive measures taken by health professionals, and the government's distribution of information via numerous sources.…”
Section: Discussioncontrasting
confidence: 89%